A pile of drums: Putting theory into practice in culturally diverse music education. (February 2020) - Walden, Jennifer
This article provides music educators with practical ways to (a) build school community through culturally diverse music and informal performances and (b) inculcate global perspectives into music programs (including concert band and choir) through culturally diverse music. In an autoethnographic style, the article tells a story that spans 2 years in a challenging situation: an international school in a country wrought with political and economic instability. It examines community building and inculcating global awareness from four perspectives. The first perspective reviews engagement in cultural diversity in music education through the lens of recently completed PhD research. It looks what scholars are writing about culturally diverse music education and how these ideas subsequently look in practice. Second, 30 years of personal experience teaching culturally diverse music are tied in, including ideas for student engagement in music classes. The third perspective includes practical ideas: how culturally diverse music can be integrated to broaden a program and rejuvenate interest in music. Finally, the fourth reveals responses from students experiencing learning through culturally diverse music. Examples, transcriptions, and recommended resources are included, leaving music teachers with useful, sustainable approaches for culturally diverse inclusivity.